Double Electron-Electron Resonance traces recorded on the CYP199A2-HaPux complex and the distances found to correspond these measurements - Bowen, A (University of Oxford, 2018)
Double Electron-Electron Resonance (DEER) traces recorded on the CYP199A2-HaPux complex and the distances determined to correspond to these measurements.